Determinants of smoking among adult residents of Felda in Negeri Sembilan, Malaysia - Ajan, Rubiahanak (2015)
Introduction: Smoking is the single most important cause of death. The use of tobacco in cigarettes among smokers is the leading cause of premature mortality and morbidity. In Malaysia itself, the main cause of mortality with 10,000 deaths reported are smoking-related diseases. Objective: The objective of the study is to determine socioeconomic determinants of smoking among adult residents of FELDA in Negeri Sembilan, Malaysia. Methods: The target population were adults from the state of Negeri Sembilan. Two FELDA areas were chosen randomly out of 38 FELDA scheme. A multistage sampling method was used to obtain the sample size. Simple random sampling was then used to select the list of house. Face to face interview was performed by using structured questionnaires. Data was collected from 1,136 respondents. The data included demographic information (age, marital status, level of education, household income), practices and economic aspects of smokers, the influence of friends and family and knowledge. Univariate, bivariate, and multivariate analysis were performed using Statistical Package for Social Sciences (SPSS) version 22.0. Result: A total of 998 respondents answered the questionnaire with a response rate 87.9%. The majority of respondents are males older than 25 years, Malay and Muslim. The findings showed that high income adults were 7.89 times more likely to exhibit smoking than low income. The higher the advertisement, the more likely it leads to increase in smoking. In addition, those who are married are 2.8 times more likely to smoke compared with those who are not married. Knowledge of smoking is one of the factors affecting smoking. Adults who are more educated are 0.57 times less likely to smoke than less educated. Married adults are more likely to smoke than the unmarried. Friends and family smokers were more likely to affect the person to smoke. Poor knowledge related to smoking may lead to smoking. The findings also showed that the higher the knowledge about smoking, the less the likelihood that they smoke. Conclusion: In conclusion, socioeconomic determinants have influenced smoking participation in Malaysia. The findings showed that 45.3% of the respondents are smoker. The prevalence of smoking among men is significantly higher compared to women. The findings also showed that there are many social determinants that could affect smoker such as friends and family members, education, employment, and knowledge. The economic determinants of smoking were advertisement and income. The social determinants were found more important and significant indicators of smoking compared with economic determinants. Based on these empirical findings, several policy implications are suggested.